SISTEM ANALISA ASET KENDARAAN DINAS KOPERASI USAHA KECIL DAN MENENGAH BERBASIS WEB - Wahyu Rizki Budiyanto; Rabiatul Adwiya; Latifah Latifah (LPPM Universitas Bina Sarana Informatika, 2021)
This study, entitled Web-Based Small And Medium Business Cooperation Vehicle Asset Analysis System aims to create a computerized system for managing vehicle asset management in which the vehicle assets are still manual. The system design method used is using the waterfall method. The tools used by front end developers use Javascript, CSS and Html, while back end developers use PHP, and the web server uses Xampp. The results of this research can make it easier to record data on official vehicles and manage them in the office of small and medium enterprises cooperatives. Keywords : Accounting Information, System, Asset, Website